An analysis of women’s activism in Goli Taraqi’s The Return within the framework of Halliday's functional linguistics - Safoora Entezari; Ebrahim Kanani; Fatemeh Zamani (مطالعات زبانی و بلاغی)
Functional linguistics is one of the theoretical linguistic trends, which emphasizes the social and contextual role of language. Michael Halliday's theory of functional linguistics analyzes words by penetrating the inner layers of the text by focusing on ideational, interpersonal and textual trans-roles. In the present research, Goli Taraqi‌'s novel, The Return (Bāzgasht), has been examined based on the theory of Halliday's functional linguistics and from the perspective of Ideational Metafunctions to explain verb processes and determine the frequency and application of each process. The main question of the research is to examine the frequency and type of application of each of the verb processes to show how these processes are reflected in the text of the novel. In fact, the purpose of the research is to investigate the role of ideational trans-role processes in shaping the semantic system of language and how it is represented in the social and cultural context of the novel. Examining the mental processes of the novel's main character, which is manifested in verbs such as thinking, feeling, seeing, etc., indicates frustrations and mental tensions of a passive woman who tries to identify the existential aspect of her character. Behavioral processes in verbs such as dreaming, wanting, making a decision, etc. indicate a change in her attitude. The material process expressed in verbs such as buying, selling, writing, going, etc., implies a change of attitude and recovery of independent female identity. Also, material and then behavioral processes have a higher frequency than mental processes. The course of the processes is also from the mental to the material.